PREDIKSI KONDISI KEUANGAN PADA PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA - Rasminiati, Ni Kadek Tina; Artini, Luh Gede Sri (E-Jurnal Manajemen, 2018)
Financial condition is a condition that shows the level of company health. Financial condition is mesuared by looking at companies experiencing financial distress and non-financial distress. The purpose of this study is to determine the effect of current asset turnover, total asset turnover, days sales in receivables, cash flow to total debt, and debt to asset to financial distress. This research is conducted at mining sector companies in Indonesia Stock Exchange year 2012-2016. The number of sample comprising 8 companies with categories financial distress and 16 companies with  categories nonfinancial distress. Data collection method using non-participant observation method and logistic regression as data analysis technique. The results of this research found that: current asset turnover has negative influence not significantly to financial distress,  total asset turnover has a negative influence significantly to financial distress, days sales in receivables has positive influence not significantly to financial distress, cash flow to total debt has negative influence not significantly to financial distress, and debt to asset has positive influence significantly to financial distress. Keywords: financial condition, financial distress, and financial ratio.